Parathyroid hormone changes following denosumab treatment in postmenopausal osteoporosis. (1st April 2013) - Makras, Polyzois; Polyzos, Stergios A.; Papatheodorou, Athanasios; Kokkoris, Panagiotis; Chatzifotiadis, Daniel; Anastasilakis, Athanasios D.
Summary: Objective: Denosumab is a new potent antiresorptive treatment of osteoporosis that can potentially induce a compensatory increase in parathyroid hormone (PTH) levels. We aimed to evaluate the alteration of PTH 1 and 6 months after denosumab's administration with different regimens of calcium and vitamin D (Ca/D) supplementation. Design: Prospective, multicenter, study in a relatively small, heterogeneous sample of postmenopausal women followed for 6 months. Patients: Forty seven postmenopausal women followed in 2 outpatient clinics, requiring onset or continuation of osteoporosis treatment. We administered 1 g calcium carbonate and 800 IU cholecalciferol daily for 6 months (Group A) or the double dose for the first month followed by the 1 g/800 IU Ca/D regimen for the next 5 months (Group B). Measurements: Parathyroid hormone (PTH) alterations between and within groups, and their associations with serum Ca and bone markers. Results: Parathyroid hormone (PTH) levels were significantly higher at month 1 and 6 only in Group A; Ca levels were significantly decreased at month 1 and returned to baseline values at month 6 within the same Group. The mean per cent change between month 1 and baseline for PTH [Δ(PTH1‐0 )] was significantly higher in Group A than B (63·5% ± 28·2% vs −3·0% ± 4·7%, P  = 0·029). Δ(PTH1‐0 ) was correlated with the reciprocal Δ‐changes of Ca ( r s  = −0·610; P  = 0·002) and collagen type I C‐terminal telopeptide ( r s  = −0·697; P  = 0·003) only in Group A. Conclusions: An increase in PTH should be expected, at least following the first administration of denosumab in common clinical practice. The effect of this compensatory onsequence in bone metabolism warrants further investigation.